Considerations for the definition of remission criteria in psoriatic arthritis - Mease, P; Coates, L (Elsevier, 2017)
Objectives Psoriatic arthritis (PsA) is an autoimmune disease that can cause progressive structural damage of the joints and irreversible disability. The potentially achievable results of biologic therapy for PsA has led to the view that disease remission should be the goal of treatment. However, the heterogeneity of disease manifestations and need for validated outcome measures makes defining remission in PsA challenging. This article evaluates proposed criteria for defining remission in PsA and discusses how these criteria can be applied in clinical practice. Methods A primary literature search was conducted in PubMed to identify articles discussing potential PsA treatment goals or targets, including minimal disease activity. English-language publications from the last 10 years were included in this assessment. Results There are 5 clinical domains in PsA that must be considered when evaluating remission: synovitis, enthesitis, dactylitis, spondylitis, and psoriasis/nail psoriasis. Due to variability in the completeness of remission and time to achieve remission with different therapies between these domains, remission should be measured clinically through a combination of objective measures, or a composite assessment tool. Composite measures are more efficient than unidimensional instruments in measuring remission, but remission rates differ between the available composite indices. Conclusion Although the concept of remission as a treatment goal in PsA is gaining acceptance among rheumatologists, further work is necessary to develop a broadly acceptable definition of remission.